Keragaman morfologi selama perkembangan embrio somatik sagu (Metroxylon sagu Rottb.) Morphological variations during the development of somatic embryos of sago (Metroxylon sagu Rottb.) - Pauline Destinugrainy KASI; . SUMARYONO (INDONESIAN OIL PALM RESEARCH INSTITUTE, 2006)
Summary In vitro culture of sago (Metroxylon sagu Rottb.) on an agar-solidified medium consists of somatic embryos of different sizes, colors, and developmental stages. One gram of mostly globular somatic embryos were cultured on a solid medium to observe their morphological variations with respect to embryo size, color, and developmental stage over one passage of six weeks culture. The medium was a modified-MS medium with half-strength of macronutrients containing 0.01 mg/L ABA and 2 mg/L kinetin. At the end of culture passage, fresh weight of embryo increased by 2.3 folds. The embryo numbers increased by more than two times indicating the formation of secondary embryos. The average size of sago somatic embryos did not change significantly over the culture period; however, the embryo size was already highly varied at the start and increased gradually as the embryo developed. At the initial of culture, 33.7 % of the embryos were yellowish, 64.1 % were greenish, and 2.2% were reddish. By the end of the culture the composition of yellowish embryos increased to 51.2 %, greenish embryo decreased to 42.5 % and red embryos increased to 6.3 %. At the initial culture, 61 % of the embryos were at the globular, 9 % at heart-shape and 30 % at torpedo stage. Generally globular embryos developed into later-stage embryos as the culture progressed, although almost 56% of the embryos remained at the globular stage after the sixth week.Ringkasan Kultur in vitro sagu (Metroxylon sagu Rottb.) pada medium padat terdiri dari embrio somatik dalam berbagai ukuran, warna, dan fase perkembangan. Satu gram embrio somatik yang sebagian besar dalam fase globuler dikulturkan pada medium padat untuk mengamati keragaman morfologi embrio dalam hal ukuran, warna dan fase perkembangan dalam satu periode kultur enam minggu. Medium kultur adalah MS modifikasi dengan setengah hara makro serta penambahan zat pengatur tumbuh ABA 0,01 mg/L dan kinetin 2 mg/L. Pada akhir masa kultur bobot embrio segar meningkat 2,3 kali dibandingkan awal masa kultur. Jumlah embrio juga mengalami peningkatan sebesar lebih dari dua kali yang menunjukkan adanya pembentukan embrio somatik sekunder. Ukuran rata-rata embrio tidak berubah secara signifikan selama masa kultur akan tetapi ukuran embrio telah sangat beragam pada awal kultur dan terus meningkat hingga akhir kultur. Warna embrio mengalami perubahan selama periode kultur. Pada awal kultur dijumpai 33,7 % embrio berwarna kuning, 64,1 % embrio hijau, dan 2,2 % embrio merah. Pada akhir kultur presentase embrio kuning meningkat menjadi 51,2 %, embrio hijau menjadi 42,5 %, dan embrio merah 6,3 %. Pada awal kultur, dijumpai 61 % embrio pada fase globuler, 9 % fase bentuk-hati dan 30 % fase torpedo. Umumnya embrio globuler berkembang menjadi embrio fase lanjut selama kultur berlangsung, namun 56 % embrio masih tetap dalam fase globuler pada minggu keenam.